Integrasi Administrasi Pembelajaran Berbasis Teknologi Informasi Model Blended Learning : - Dian Nafi Firdhaus Dian Nafi Firdhaus; Andi Prastowo (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2021)
The development of information and communication technology is happening so fast. Information technology must be used wisely in providing benefits, especially science. Information technology-based learning also has problems, especially in the application of its learning. This requires effort to be combined with face-to-face learning, with the aim that the learning process does not only depend on information technology, with the current conditions in Indonesia that implement Social Distancing due to the Covid 19 virus, online learning is the right solution for now. Based on background above, the researcher can take a problem formulation about blended learning and how the basic concepts, learning syntax and factors exist in blended learning. In this research, the researcher uses qualitative research methods and a case study approach as well as data collection techniques using purposive sampling and snowball sampling, in obtaining data in the study.